Catch per unit effort (CPUE) and population dynamics of Japanese threadfin bream (Nemipterus japonicus) at coastal area of Sungai Besar, Selangor - Kama Nadzha, Muhammad Afiq (2013)
Nemipterus japonicus is the demersal commercial fish which also known as Japanese threadfin bream. In Malaysia, threadfin bream is more in the food industry. As the demand of the market is high, the population of the fish in the sea around Malaysia has decrease due to the overfishing activities and also the degradation of the biology parameter in west coast of peninsular Malaysia. The objectives of the study are to determine the population dynamics based on the length-weight parameter and estimating the catch per unit effort (CPUE) per boat. The study was conducted at Sungai Besar (3° 40' 0" North, 100° 59' 0" East), Selangor. Samplings were carried out between January 2013 and October 2013. The samples being collected consists of 60 to 100 individuals. Boat from class B or C was used for determining the catch per unit effort (CPUE). The asymptotic length (L∞) was 28.88 cm and growth co-efficient (K) was 0.42 year-1. The growth performance index (φ') was 2.54. The value of total mortality (Z), natural mortality (M) and fishing mortality (F) were 2.334 year-1, 1.039 year-1and 1.295 year-1 respectively. The exploitation level (E) was 0.555. Recruitment pattern was along the year where the highest in September – October with percentage of 17.06 %. The value of growth coefficient (b) and coefficient of determination (r2) were 2.8755 (±0.02) and 0.8583 respectively. The CPUE value was 0.000167 kg h-1 L-1. The result showed that the stock of the Nemipterus japonicus was over exploited.